Propuesta de diseño para acondicionamiento acústico y electroacústica en la iglesia de la Inmaculada Concepción - Guaygua Toapanta, Ricardo Andrés (2012)
The work involves developing a design proposal for conditioning and electro-acoustic sound in the Church of the Inmaculada Concepcion, located on the Prensa Avenue, between Pedro Traversari SO3-75 and Captain Francisco Oliva, building on the theoretical basis on soundproofing existing and electro-acoustic. The Church is dedicated to performing choral events like presentations, symphonic and social activities for the sole purpose of calling and involves people in the community, which has become indispensable electronic and acoustic properties for optimal events of this magnitude. For the study will be used ISO standards enabling us to evaluate the acoustics of the place and easily applicable to the reality and may well start a proper planning in the preparation of the proposal. To assess the situation of the Church acoustic measurements previously made in situ, inside architectural surveys, evaluation of existing materials on site and the electro-acoustic field an inventory of electronic tools that exist in the place in order to find solutions more efficient and less costly to design.